Effect of station format on the psychometric properties of Multiple Mini Interviews. Issue 10 (22nd June 2022) - Renaud, Jean‐Sébastien; Bourget, Martine; St‐Onge, Christina; Eva, Kevin W.; Tavares, Walter; Salvador Loye, Alexis; Leduc, Jean‐Michel; Homer, Matt
Abstract: Background: Given the widespread use of Multiple Mini Interviews (MMIs), their impact on the selection of candidates and the considerable resources invested in preparing and administering them, it is essential to ensure their quality. Given the variety of station formats used and the degree to which that factor resides in the control of training programmes that we know so little about, format's effect on MMI quality is a considerable oversight. This study assessed the effect of two popular station formats (interview vs. role‐play) on the psychometric properties of MMIs. Methods: We analysed candidate data from the first 8 years of the Integrated French MMIs (IF‐MMI) (2010–2017, n  = 11 761 applicants), an MMI organised yearly by three francophone universities and administered at four testing sites located in two Canadian provinces. There were 84 role‐play and 96 interview stations administered, totalling 180 stations. Mixed design analyses of variance (ANOVAs) were used to test the effect of station format on candidates' scores and stations' discrimination. Cronbach's alpha coefficients for interview and role‐play stations were also compared. Predictive validity of both station formats was estimated with a mixed multiple linear regression model testing the relation between interview and role‐play scores with average clerkship performance for those who gained entry to medical school ( n  = 462). Results: Role‐play stations ( M  = 20.67, standard deviation [ SD ] = 3.38) had a slightly lower mean score than interview stations ( M  = 21.36, SD  = 3.08), p  < 0.01, Cohen's d  = 0.2. The correlation between role‐play and interview stations scores was r  = 0.5 ( p  < 0.01). Discrimination coefficients, Cronbach's alpha and predictive validity statistics did not vary by station format. Conclusion: Interview and role‐play stations have comparable psychometric properties, suggesting format to be interchangeable. Programmes should select station format based on match to the personal qualities for which they are trying to select. Abstract : Renaud et al. found that interview and role‐play stations in Multiple Mini Interviews have comparable psychometric properties, suggesting station format to be interchangeable.